Highly conductive single-molecule junctions through electrocatalytic formation of benzyl-type Au‒C bonds - Yaxuan Zhang; Kai Qu; Ting Pan; Yaqi Zhang; Leng Wang; Hongliang Chen (Nature Communications)
Abstract Creating reliable molecular-scale electronic devices demands strong, stable connections between metal electrodes and organic molecules. A significant challenge is forming robust chemical bonds directly to gold electrodes, as gold is notoriously unreactive. Conventional methods for creating gold-carbon (Au‒C) bonds are therefore limited. Here we demonstrate an electrocatalytic solution: using an applied voltage, we inject a single electron from a gold electrode into specific organic salts (pyridinium ions). This electron transfer breaks the salt apart, generating highly reactive carbon-based radicals. These radicals spontaneously form strong, direct covalent bonds (Au‒C) with the gold surface. Using precise single-molecule measurements, we show this radical-mediated bonding creates exceptionally stable molecular junctions. Furthermore, these junctions exhibit excellent electrical conductivity across the molecule’s core structure. This high conductivity arises because the direct Au‒C bond allows efficient overlap of electron orbitals between the gold and the molecule. Our strategy provides a versatile and controlled way to build atomically precise, highly conductive interfaces between metals and organic components, advancing the design of functional molecular electronics through tailored covalent connections.